A new architecture of Low Impact Development (LID)-based stormwater management system through Internet of Things (IoT) and Machine Learning integration - Ismail Essamlali; Hasna Nhaila; Mohamed El Khaili (Case Studies in Chemical and Environmental Engineering)
Bouznika, Morocco, is grappling with severe stormwater management challenges stemming from rapid urbanization. Increased impervious surfaces, inadequate drainage infrastructure, and intense rainfall events have led to frequent flooding, erosion, and water pollution. This paper explores the potential of Low Impact Development (LID) strategies to mitigate these issues and contribute to achieving Sustainable Development Goal 6. By evaluating various LID techniques for their runoff reduction efficacy, we propose an integrated approach combining LID with Internet of Things (IoT) and Machine Learning (ML) technologies to optimize stormwater management in Bouznika.